Growth, lipid content, and lipid profile of the green alga, chlorella vulgaris beij., under different concentrations of FE and CO2 - Carpio, Rowena B. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
This study describes the effects of different concentrations of Fe+3 in the growth medium (2.4E-05 mol/L and 4.8E-05 mol/L as Ferric-citrate) and CO¬2 (0.036%, 1% and 2% as CO¬2 in air) on the growth, total lipid (TL) content, total lipid production (TLP) and fatty acid (FA) profile of the green alga, Chlorella vulgaris Beij, in vitro. High-Fe+3 (4.8E-05 mol/L) plus 2% CO¬2 provided the best growth for the alga with 460.0 ± 10 mg/L dry biomass, while the culture with low-Fe+3 (2.4E-05 mol/L) plus 2% CO¬2 provided the maximum TL content of 27.0 ± 10 %. The highest TLP was obtained from high-Fe+3 (4.8E-05 mol/L) with 1% CO¬2, and low-Fe+3 (2.4E-05 mol/L) with 2% CO¬2; at 117.8 ± 5.6 mg/L and 115.1 ± 6.1 mg/L, respectively. Both of these lipids displayed a FA profile suitable for biodiesel production, with the later condition giving superior fuel property, in terms of IV, CN and viscocity, satisfying the specifications by both the European (EN 14214) and US (ASTM B100) standards. The study shows the possibility of modifying lipid composition in freshwater green alga, Chlorella vulgaris Beij by varying the concentrations of CO¬2 in aeration and Fe+3 in the growth medium.
Thesis (M.S. Energy Engineering)--University of the Philippines, Diliman.
Keywords: Fuel switching; Microalgae; Chlorella